Transport Vesicle Tethering at the Trans Golgi Network: Coiled Coil Proteins in Action - Cheung, Pak-yan P.; Pfeffer, Suzanne R. (Frontiers in Cell and Developmental Biology, 2016)
The Golgi complex is decorated with so-called Golgin proteins that share a common feature: a large proportion of their amino acid sequences are predicted to form coiled-coil structures. The possible presence of extensive coiled coils implies that these proteins are highly elongated molecules that can extend a significant distance from the Golgi surface. This property would help them to capture or trap inbound transport vesicles and to tether Golgi mini-stacks together. This review will summarize our current understanding of coiled coil tethers that are needed for the receipt of transport vesicles at the trans Golgi network (TGN). How do long tethering proteins actually catch vesicles? Golgi-associated, coiled coil tethers contain numerous binding sites for small GTPases, SNARE proteins, and vesicle coat proteins. How are these interactions coordinated and are any or all of them important for the tethering process? Progress toward understanding these questions and remaining, unresolved mysteries will be discussed.